UPAYA PENINGKATAN KUALITAS CITRA MRI DENGAN PEMBERIAN MEDIA KONTRAS - Suhardi Suhardi; Wahyu Setiabudi; Choirul Anam (BERKALA FISIKA, 2013)
Improvement the image quality of magnetic resonance imaging (MRI) carried out bycontrast media has been done. It was expected to obtain a better image quality so thatinterpretation of MRI images more valid. Contrast media were used gadolinium 5 mmol/10 ml perpatient. Number of patients 10 people with tumor of the head, and each uses a 6 slices. MRI usedAIRIS II with 0.3 Tesla magnetic field, Kodak Dry View 8900, densitometry, and Film. In thisstudy, the image resulted with and without contrast media were measured its density andcompared. It was resulted that the image density in normal tissues no change, with and withoutcontrast media. While the tumor area with and without contrast media, the density decreased byan average of 0,56. The addition of contrast media, the presence of tumor will appear moreclearly.Keywords: Contrast Media, gadolinium, MRI